Responsabilidad del Estado colombiano en accidentes de tránsito por el mal estado de las vías - Cabrera Suárez, Lizandro Alfonso (DIXI, 2019)
Objective: the work makes an analysis of the responsibility of the State in traffic accidents generated by the poor state of the roads, starting from a characterization of the issue of responsibility. Methodology: based in a theoretical foundation and a state of the art on the subject. The article presents a brief study from the comparative law in the research subject. Outcome: finally, it defends a contrary position in which there is not always an objective responsibility of the public administration. Conclussion: among other, verification of the poor condition of the roads does not generate State responsibility